Una nuova avventura - Ciotti, Fabio (Umanistica Digitale, 2017)
Nowadays the creation of a new journal might seem a difficult choice, or even a matter of vanity. it appears as a loss of both intellectual energies and economical assets. The landscape of scientific publications in Italy is strictly related to local and disciplinary boundaries. In particular, in the academic context such an adventure should be discouraged, because of the limits imposed by the evaluation process of scientific activities. Nevertheless, the Associazione per l’Informatica Umanistica e la Cultura Digitale (AIUCD) is keen to accept the challenge and to set a new journal: Umanistica Digitale. First of all, it is an online and open access journal. Despite any doubt, we believe we need to change the current situation and give everybody free access to knowledge.